2001
DOI: 10.1053/jhep.2001.29626
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus X protein transactivates inducible nitric oxide synthase gene promoter through the proximal nuclear factor [kappa ]B[ndash ]binding site: Evidence that cytoplasmic location of X protein is essential for gene transactivation

Abstract: Nitric oxide appears to play a central role in the pathogenesis of many inflammatory disorders. We have previously shown that there is an enhanced intrahepatic expression of the inducible nitric oxide synthase (iNOS) gene during chronic hepatitis B virus infection, and that viral X protein (HBx) transcriptionally activates this cellular gene, but the molecular basis for this activation remains to be defined. We aimed to explore the involvement of different cis-acting elements of the human iNOS promoter in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…The expression of HBx in samples with serum HBV-negative implicated quite a few patients were once infected with HBV. Moreover, the cytoplasmic location of HBx was consistent with the previous reports [15] . NF-κB plays a vital role in almost all aspects of cell regulation such as immune cell activation, proliferation, apoptosis, stress response, differentiation and oncogenic transformation.…”
Section: Discussionsupporting
confidence: 92%
“…The expression of HBx in samples with serum HBV-negative implicated quite a few patients were once infected with HBV. Moreover, the cytoplasmic location of HBx was consistent with the previous reports [15] . NF-κB plays a vital role in almost all aspects of cell regulation such as immune cell activation, proliferation, apoptosis, stress response, differentiation and oncogenic transformation.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, HBx activates NF-B signaling (12,13) and enhances the expression of its downstream inflammatory targets, including inducible nitric-oxide synthase (iNOS) (9, 14 -16). Inducible NOS is both an NF-B-responsive (17)(18)(19)(20) and an HBx-regulated gene (14). Inducible NOS generates nitric oxide (NO) from L-arginine.…”
mentioning
confidence: 99%
“…The functional activity and subcellular distribution of HBx seemed to be controlled by its phosphorylation status, e.g., mediated by ERK1/2 [18,40] . It has been reported that cytoplasmic HBx is involved in the activation of iNOS, a factor that plays an important role in inflammatory disorders and regulation of the Ras-Map kinase signaling [35,41,42] . Nuclear localization of the HBx protein has been shown to modulate the activity of cellular factors like AP-1, NF-B, tumor suppressor P53, DDB proteins (damaged DNA binding protein), and p21(WAF1/Cip1) [40,43] .…”
Section: Discussionmentioning
confidence: 99%